The Wellsprings of wisdom : a study of Abū Yaʻqūb al-Sijistānī's Kitāb al-Yanābīʻ : including a complete English translation with commentary and notes on the Arabic text - Walker, Paul Ernest, 1941- (University of Utah Press, 1994)
The rapid success of the early Isma'ili dacwa, or religio-political mission, culminated in the establishment of the Fatimid caliphate in the year 909. Modern scholarship in Ismaʹili studies has revealed that the Ismaʹilis were also engaged from early on in their eventful history in diverse intellectual activities, some of which were unique to the Ismaʹili community. In particular, while the early Fatimid caliph-imams were still preoccupied with consolidating the power base of their dawla in North Africa, some of the Ismaʹili daʹis of the Iranian lands elaborated a distinctive Isma'ili tradition of learning, amalgamating in a highly original fashion their Ismaʹili interpretation of Islam with a type of Neoplatonic philosophy then current in Khurasan and some other eastern regions of the Muslim world. -- from http://www.jstor.org (Nov. 16, 2013).